2004
DOI: 10.1086/425016
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Cytokine Network and Unfavorable Outcome in Patients with Yellow Fever

Abstract: To study the contribution of inflammatory mediators to the pathogenesis of yellow fever (YF), the serum levels of several cytokines and chemokines were measured in 7 patients with fatal YF (f-YF), 11 patients with nonfatal hemorrhagic YF (nf/h-YF), and 18 patients with nonfatal nonhemorrhagic YF (nf/nh-YF). The levels of interleukin (IL)-6, monocyte chemoattractant protein-1, interferon-inducible protein (IP)-10, tumor necrosis factor- alpha , and IL-1 receptor antagonist (IL-1RA) were all statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 32 publications
8
63
0
6
Order By: Relevance
“…Additionally, YFV-17D RNA was only detected in approximately half of patients with fatal YFV-AVD (Bae et al, 2008;Monath et al, 2013;ter Meulen et al, 2004). Similarly, we found that viral titres at disease onset did not correlate with disease outcome.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Additionally, YFV-17D RNA was only detected in approximately half of patients with fatal YFV-AVD (Bae et al, 2008;Monath et al, 2013;ter Meulen et al, 2004). Similarly, we found that viral titres at disease onset did not correlate with disease outcome.…”
Section: Discussionmentioning
confidence: 58%
“…In humans, severe DENV, YFV and YFV-17D-associated viscerotropic disease are potentially mediated by dysregulated secretion of cytokines and chemokines (Bae et al, 2008;Lee et al, 2006b;Monath, 2008;ter Meulen et al, 2004). We found significantly elevated serum levels of IP-10 and MCP-1 in mice with viscerotropic disease as compared with mice with neurotropic disease and mice displaying no clinical signs of disease (Fig.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations